"The Cockroaches of Canada"1: French‐Canada, Immigration and Nationalism, Anti‐Catholicism in English‐Canada, 1905–1929. (5th November 2014) - Anderson, Kevin
<x xml:space="preserve">Abstract</x> This article examines the central influence of anti‐Catholicism upon English‐Canadian nationalism in the first third of the twentieth century. Anti‐Catholicism provided an existing rhetorical and ideological tradition and framework within which public figures, intellectuals, Protestant church leaders and other Canadians communicated their diverse visions of an ideal Canada. The study of anti‐Catholicism problematises the rigid separation that many scholars have posited between a conservative ethnic nationalism and a progressive civic nationalism. Often times these very civic values were inextricable from a context of Britishness. In addition, anti‐Catholicism was not simply about theological differences between Protestants and Catholics. Instead this theological thread often intersected with the perceived socio‐political problems that Catholics and Catholicism posed. Hostility to Catholicism was not limited only to fraternal organisations such as the Orange Order; indeed the importance of anti‐Catholicism as a component of Canadian nationalism lies in its presence across the political and intellectual spectrum. Catholicism was perceived to inculcate values antithetical to British traditions of freedom and democracy.